Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Vicin, Logan; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Injections of 200 mg of iron are commonplace when trying to prevent iron deficiency in piglets, but there is concern over the level of iron provided from one injection compared to an injection along with a booster. The purpose of this study was to evaluate the effects of increasing dosage of Gleptoforte in newborn pigs on sow and litter performance. The main objective is to find out the appropriate amount(s) of Gleptoforte that when administered by injection provide the greatest growth performance and health in newborn piglets. 336 newborn piglets were used in a 21 day study, in which 28 litters were used with the number of pigs per sow were equalized. Shortly after birth, all pigs were weighed and assigned treatments through a completely randomized design with 56 piglets per treatment. The treatments included a negative control of no iron injection, along with increasing levels of Gleptoforte: 50, 100, 150, or 200 mg plus a 100 mg booster. Pigs were weighed to calculate body weight and average daily gain, and blood collection via jugular venipuncture took place on day 3, 11, and 21 to measure Hemoglobin, Hematocrit, Serum Fe, and Total Iron Binding Capacity. Overall, ADG and body weight increased as the dosage of Gleptoforte increased. There was no evidence of difference in performance in all three periods between the 200 mg and 200 mg plus 100 mg injections, which suggests that the booster at day 11 did not provide any additional benefits compared to the 200 mg injection with no booster. There was no evidence of difference observed of hematological data measured on day 3 prior to iron injection. The most significant difference (P=.011) in hemoglobin was observed on day 21 with 200 mg plus 100 mg injection having a higher value than the 200 mg alone. Overall, as expected the negative control had the least results, however the 100 mg injection showed the greatest growth performance. These tests reveal that over time there are clearly certain injections that provide greater benefits in comparison to others, but this study also reveals that further testing must be done in order to clearly determine the optimal days to inject along with the optimal level of dosage.
Keywords: Fall 2017